Changing identifications and alliances in North-East Africa. - Schlee, Günther; Watson, Elizabeth E., 1968- (Integration and conflict studies, 2009)
Forms of group identity play a prominent role in everyday lives and politics in north-east Africa. These volumes provide an interdisciplinary account of the nature and significance of ethnic, religious, and national identity in north-east Africa. Case studies from Sudan, Ethiopia, Uganda, and Kenya illustrate the way that identities are formed and change over time, and how local, national, and international politics are interwoven. Specific attention is paid to the impact of modern weaponry, new technologies, religious conversion, food and land shortages, international borders, civil war, and displacement on group identities. Drawing on the expertise of anthropologists, historians and geographers, these volumes provide a significant account of a society profoundly shaped by identity politics and contribute to a better understanding of the nature of conflict and war, and forms of alliance and peacemaking, thus providing a comprehensive portrait of this troubled region.